Technology, the global economy and other new challenges for civil justice - Miki, Kōichi, 1958-; International Association of Procedural Law; International Association of Procedural Law. Conference 2019 : Kobe, Japan) (Cambridge : Intersentia, 2021)
This is a fresh and stimulating book on new challenges for civil justice. It brings together leading experts from across the world to discuss relevant topics of civil justice from regional, cross-border, international and comparative perspectives. Inter alia, this book will focus on multinational rules and systems of dispute resolution in the era of a global economy, while also exploring accountability and transparency in the course of civil justice. Transnational cooperation in cross-border insolvency, regionalism in the process of recognition and enforcement of foreign titles, and the application of electronic technologies in judicial proceedings, including new types of evidence also play a major role. Technology, the Global Economy and other New Challenges for Civil Justice is a compact and accessible overview of new developments in the field from across the world and written for those with an interest in civil justice.
Title from publisher's bibliographic system (viewed on 10 Dec 2021).
"The 16th World Congress of the International Association of Procedural Law, held from November 2nd to 5th, 2019 in Kobe, Japan ... This volume presents the papers presented at the Congress"--Page v.
Keywords: Technology and law -- Congresses; International economic relations -- Law and legislation -- Congresses; Due process of law -- Congresses